Chemical injuries from assaults: An increasing trend in a developing country - Peter B. Olaitan; Bernard C Jiburm (Indian Journal of Plastic Surgery)
Objective: This paper describes chemical injuries, which presented to us and were managed at a burn unit in Nigeria. The purpose of this paper is to highlight the etiologies of these injuries, the extent of the injuries as well as to suggest possible ways to prevent chemical injuries in our environment.Materials and Methods: We carried out a retrospective review of chemical burns treated at our center. Our sources of information were the burn unit admission registers, case notes of the patients and operation registers. The results were collated and then analyzed.Results: Twenty eight patients presented with chemical burn injuries during the study period between January 2000 and December 2003, constituting 5.7% of all patients with burns treated within that period. Seventeen (60.7%) of the patients were males while 11 (29.3%) were females with a mean age of 20.6 years. The injuries were sustained from assault in 21 (75%), armed robbery attacks in five (17.8%) and suicide attempts in two (7.1%). The agents were usually unknown. Late presentation was observed in all the patients. Raw eggs, palm oil, gentian violet and engine oil were the substances applied immediately after the injuries. Complications observed included septicemia, respiratory distress, blindness, renal failure, mentosternal contractures, ectropion, axillary contractures, hypertrophic scars, keloids and skin depigmentation.Conclusion: Chemical burn injuries are mainly due to assaults in Nigeria and are usually extensive and presented late. Education of the people and penalty for any offender will reduce the current spate of such injuries.